Governance and accounting practices in hybrid organizations: Insights from a sixteenth-century charity in Venice. (August 2019) - Lusiani, Maria; Vedovato, Marco; Pancot, Chiara
This article explores governance and accounting practices in hybrid organizations. Currently, hybrid organizations represent an increasingly pervasive phenomenon, but their role has also been central in the past. To achieve this aim, we consider the case of a charity, the Scuola Grande di San Rocco, as its activity grew in scope and complexity during the sixteenth century in the Republic of Venice. The Scuole Grandi represents a form of hybrid organizations because these charities were privately managed, but publicly regulated. They shared a devotional orientation and performed de facto welfare functions in progressive integration with the State. Based on an analysis of balance sheets and administrative documents, this article aims to discuss the role of governance and accounting in enabling hybrid organizations to operate through multiple logics.